2006
DOI: 10.1210/jc.2005-1878
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Peptide YY Levels in Adolescent Girls with Anorexia Nervosa

Abstract: Elevated PYY may contribute to reduced intake and decreased bone turnover in AN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
137
0
8

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 227 publications
(160 citation statements)
references
References 35 publications
15
137
0
8
Order By: Relevance
“…Changes in PYY levels with weight gain are conflicting, with one reporting a decrease [24] and the other no change [25] in PYY levels following an increase in weight. Our group has shown that in adolescent girls with anorexia nervosa, BMI and PYY levels were inversely correlated, and a trend toward a decrease in PYY levels followed weight recovery [22]. Our data show an inverse association between BMI and PYY levels in adult women with anorexia nervosa.…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations
“…Changes in PYY levels with weight gain are conflicting, with one reporting a decrease [24] and the other no change [25] in PYY levels following an increase in weight. Our group has shown that in adolescent girls with anorexia nervosa, BMI and PYY levels were inversely correlated, and a trend toward a decrease in PYY levels followed weight recovery [22]. Our data show an inverse association between BMI and PYY levels in adult women with anorexia nervosa.…”
Section: Discussionsupporting
confidence: 58%
“…Therefore mechanisms leading to bone loss are important to identify. Several previous studies have suggested that females with anorexia nervosa have elevated PYY levels relative to normal weight or obese individuals [22][23][24][25]. This is the first study to demonstrate a strong association between elevated PYY values and lower BMD in women with anorexia nervosa, suggesting a possible contribution of PYY to the severely low BMD found in this disorder.…”
Section: Introductionsupporting
confidence: 50%
See 2 more Smart Citations
“…In contrast to OB subjects, increased fasting and meal-stimulated PYY levels are present in patients with anorexia nervosa (AN), suggesting that the peptide may play a physiopathological role in this eating disorder (34)(35)(36)(37).…”
Section: Introductionmentioning
confidence: 99%